Environmental indicators in salmon aquaculture research: A systematic review. (29th June 2021) - Rector, Megan E.; Weitzman, Jenny; Filgueira, Ramón; Grant, Jon
Abstract: The ecosystem approach to aquaculture (EAA) is a strategy for the sustainable development of the aquaculture sector, but the question of how it can be practically implemented remains unclear. Indicators that can be applied at relevant scales of impact and that reflect the environmental status and change offer a means of operationalizing EAA. Therefore, a systematic literature review was carried out to identify environmental indicators referenced in salmon aquaculture literature and review their potential to support EAA. Using the PRISMA method for selecting journal papers, 101 articles that included 531 indicators were reviewed. Indicators were characterized based on the effect of aquaculture they measure, their similarity to other indicators extracted, and the scale at which they were applied. Indicators and their characteristics are presented in a searchable online database. A scoring method for evaluating indicators based on criteria drawn from environmental indicator literature and the potential scalability of indicators to meet the needs of EAA was developed and applied to the most frequently referenced indicators. Overall, near‐field indicators of benthic impacts dominated salmon aquaculture literature. Of the most frequently referenced indicators, those that scored highest based on criteria drawn from environmental indicator literature also scored highest on scalability and therefore their potential contribution to EAA. Overall, results suggest that additional research and application of far‐field environmental indicators in salmon aquaculture will be required to identify a suite of indicators that can be applied as part of EAA practice.